2008
DOI: 10.3382/ps.2007-00192
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Breaking Strength of White Leghorns Housed in Conventional, Modified, and Commercially Available Colony Battery Cages

Abstract: Limited opportunity for movement and load-bearing exercise for conventionally caged laying hens leads to bone loss and increased susceptibility to osteoporosis, bone fractures, and cage layer fatigue, all of which compromise hen welfare and have negative consequences for production. The objective of this study was to compare bone mineral density (BMD) and strength measures of White Leghorns housed in conventional battery cages (CONV), cages modified to incorporate a nest box and perch (MOD), and commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 39 publications
7
50
1
3
Order By: Relevance
“…Tibiae were cradled on two support points measuring 4 cm apart. A force was applied to the midpoint of the same face of each tibia using a 50 kg load cell with a crosshead speed of 10 mm min -1 (Jendral et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Tibiae were cradled on two support points measuring 4 cm apart. A force was applied to the midpoint of the same face of each tibia using a 50 kg load cell with a crosshead speed of 10 mm min -1 (Jendral et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Data from a number of studies revealed differences in egg quality depending on the housing system. Moorthy et al (2000), Leyendecker et al (2001a) and Jenderal et al (2004) reported higher egg weights in cages, while Tůmová and Ebeid (2005), Pištěková et al (2006), Zemková et al (2007) found out heavier eggs on litter. Quality traits such as egg shell thickness, Haugh unit score and yolk index were reported to be higher in cages than on litter (Roland et al, 1997;Moorthy et al, 2000;Tůmová and Ebeid, 2005;Lichovníková and Zeman, 2008).…”
mentioning
confidence: 95%
“…Previous studies have suggested that perch use can maintain the strength of the leg bones of laying hens [16,18] and that this is a function of maintaining bone volume [17] and density [20]. Nevertheless, in a comparison among laying hens housed in unfurnished and furnished cages there were no significant affects of the housing conditions on the weight, breaking strength, elastic strain or stiffness of the humerus [21].…”
Section: Discussionmentioning
confidence: 80%
“…Bone mineralization can be accurately and precisely measured by quantitative computer tomography (QCT) scans. This technique has previously been used to assess mineralization of the bones of laying hens at the end of the production cycle [19] and in response to housing conditions [20]. In the present study, the effect of cage enrichment, i.e.…”
Section: Introductionmentioning
confidence: 89%